PENGARUH PERUBAHAN TUTUPAN LAHAN DI DAERAH ALIRAN SUNGAI BENGAWAN SOLO TERHADAP FUNGSI PENGENDALIAN BANJIR SURAKARTA 2023 - Callista Fabiola Candraningtyas; Lathifa Putri Wiedhya Syahrani; Luthfia Luthfia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
In February, flooding struck Surakarta City as a result of the recent intense rain. Opening the sluice of the Gajah Mungkur Dam is an alternative as the Wonogiri area upstream of the Bengawan Solo watershed is no longer able to handle the flow. This resulted in the Bengawan Solo River being unable to handle the flow and overflowing due to an increase in tributary discharge in Sukoharjo and Surakarta. The goal of this essay is to assess how changes in land use affect the watershed's ability to regulate itself in the Bengawan Solo (DAS). To identify land changes that were in place, this study used secondary data in the form of rainfall and land cover data that were processed using ArcGIS 10.8 software. The analysis of the data was done utilizing a mixed descriptive approach. The result of this study is that changes in land use have a significant impact on Surakarta's ability to regulate floods.